Prevention and Safety for the Return to Face-to-face Physical Education Classes During Covid-19: Differences by Gender and Professional Training - Ceballos-Gurrola, Oswaldo (2024)
Objective: The aim of this study was to analyse Mexican physical education teachers' level of knowledge of prevention and safety recommendations for returning to classroom instruction after COVID-19 confinement, and to determine whether there were differences according to gender and type of professional training. Methods: A total of 669 teachers (Mage = 40.33 years, SD = 10.26) responded to an ad hoc questionnaire. Results: The results showed high mean scores for prevention and safety measures, with hygiene recommendations being the highest (M = 6.52), while the use of technology was the lowest (M = 5.32). Significant differences were only found for professional training in hygiene recommendations (p < .05; Hedges' g = 0.09), while there were no statistically significant differences according to gender in any of the factors. Conclusion: There seems to be a broad recognition of safety measures for COVID-19 prevention by the teachers participating in this research, however, studies with different methodologies are needed to confirm these findings.